Space, Time and Abstract Relations in the Coffin Texts - Zamacona, Carlos Gracia (Zeitschrift für ägyptische Sprache und Altertumskunde, 2010)
This paper briefly proposes a semantic approach to a cross-linguistically well known phenomenon: the use of the expression of space–situation or motion–to express temporal and abstract relations–cause, characterization and finality. The study is the result of a thoroughly analysis of data from the Coffin Texts.